2018
DOI: 10.2138/am-2018-6546ccby
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution analysis of the iron oxidation state in silicate glasses using the electron probe

Abstract: The iron oxidation state in silicate melts is important for understanding their physical properties, although it is most often used to estimate the oxygen fugacity of magmatic systems. Often high spatial resolution analyses are required, yet the available techniques, such as μXANES and μMössbauer, require synchrotron access. The flank method is an electron probe technique with the potential to measure Fe oxidation state at high spatial resolution but requires careful method development to reduce errors related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…A particular challenge with using Eq. (1) is the need to know the Fe 3+ content of the silicate melt, which is not readily measurable by conventional electron microprobe techniques (see review by Hughes et al 2018). Olivine contains negligible Fe 3+ (less then a few thousand ppm and not more than a few percent of the total Fe, Fe T ; Ejima et al 2018) so that where Fe 3+ in the melt is low, i.e., in relatively reduced systems, Kd Fe 2+ −Mg can be used with confidence assuming that Fe 2+ = Fe T .…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A particular challenge with using Eq. (1) is the need to know the Fe 3+ content of the silicate melt, which is not readily measurable by conventional electron microprobe techniques (see review by Hughes et al 2018). Olivine contains negligible Fe 3+ (less then a few thousand ppm and not more than a few percent of the total Fe, Fe T ; Ejima et al 2018) so that where Fe 3+ in the melt is low, i.e., in relatively reduced systems, Kd Fe 2+ −Mg can be used with confidence assuming that Fe 2+ = Fe T .…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…4), probably due to the smaller spot size of µXANES (i.e., greater flux density) compared to the SMS simulation. The mechanism of oxidation is not clear, but may involve the formation of tiny magnetite nanolites (Di Genova et al 2017;Hughes et al 2018), as suggested by Raman spectra of some µXANES spots and the darkening of the glass after irradiation. This mechanism may operate in tandem with the alkali migration proposed above.…”
Section: Ferric-ferrous Ratiosmentioning
confidence: 99%
“…The peaks of the L series emitted from the metals of first order transition are the result of electronic transitions between the 3d orbitals partially filled and the 2p core levels (L 2,3 ). Different methods are based on the analysis of the Fe L α,β emission spectra of minerals and glasses to measure their Fe 3+ /Fe TOT (Höfer et al, 1994, Fialin et al, 2001, 2004, Zhang, Almeev, et al, 2018Hughes et al, 2018Hughes et al, , 2020.…”
Section: Electronic Microprobementioning
confidence: 99%
“…Examples of such unwanted effects are self-absorption or induced beam damage (i.e., see for sulfur Metrich et al, 2002Metrich et al, , 2003Metrich et al, , 2010andfor iron Goncalves et al, 2013, andCottrell et al, 2018;Hughes et al 2018Hughes et al , 2020. Finally, the accuracy of the experiment will depend on the standard used and on how the sample is prepared.…”
Section: Advantages Drawbacks Accuracymentioning
confidence: 99%
“…Silicate glass can become unstable during EPMA due to the diffusive migration of mobile elements (e.g., Na), sometimes referred to as 'beam damage' (e.g., Nielsen and Sigurdsson, 1981). Glass composition controls the severity of beam damage and hydrous glass is more susceptible than anhydrous glass (e.g., Hughes et al, 2018;Humphreys et al, 2006;Zhang et al, 2018). Element migration can also occur in hydrous minerals, such as amphibole and apatite, causing errors in VBD estimates of these minerals (e.g., Stock et al, 2015).…”
Section: Element Migrationmentioning
confidence: 99%